9(2y-6)-(5y+3)=

Simple and best practice solution for 9(2y-6)-(5y+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2y-6)-(5y+3)= equation:


Simplifying
9(2y + -6) + -1(5y + 3) = 0

Reorder the terms:
9(-6 + 2y) + -1(5y + 3) = 0
(-6 * 9 + 2y * 9) + -1(5y + 3) = 0
(-54 + 18y) + -1(5y + 3) = 0

Reorder the terms:
-54 + 18y + -1(3 + 5y) = 0
-54 + 18y + (3 * -1 + 5y * -1) = 0
-54 + 18y + (-3 + -5y) = 0

Reorder the terms:
-54 + -3 + 18y + -5y = 0

Combine like terms: -54 + -3 = -57
-57 + 18y + -5y = 0

Combine like terms: 18y + -5y = 13y
-57 + 13y = 0

Solving
-57 + 13y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '57' to each side of the equation.
-57 + 57 + 13y = 0 + 57

Combine like terms: -57 + 57 = 0
0 + 13y = 0 + 57
13y = 0 + 57

Combine like terms: 0 + 57 = 57
13y = 57

Divide each side by '13'.
y = 4.384615385

Simplifying
y = 4.384615385

See similar equations:

| 6r^7+6r^5=0r^6+9r^4 | | (20-2x)*(40-2x)*x=x | | (v+3)(v-4)=v | | (4x+16)= | | 3(2k+4)-13k+4+2= | | 4.8x-8.4y-4.5=0 | | 0.007(x+3)=0.008x+0.0018 | | -3k+5k-5+2k= | | -.1x+2.1y=-9.7 | | 17y-73=y-4 | | 13r+s+20r+11s= | | 0.9z=13z | | -2(x-7)+7=21 | | (0)b=1 | | 17(y-73)=y-4 | | y=x^3+x^2-16x-16 | | 50x-60= | | -8+7y=-56 | | -3(3y-10)+2(2y+7)= | | 14u^2+5u-1=0 | | 2+5=0 | | -4-(3-5p)= | | 4(3z-1)-2(z+1)=7(z+1) | | -(2z+2)+3(2z+5)-2z= | | -6(n-4)+3(n+1)= | | -7(n-2)+4(n+1)= | | 174=30+12y | | 3=5p(4q-1) | | N+3(n-1)= | | -5x+10x=20 | | 0.5x+0.20(9.0*x)=4.20 | | Ad+9-d-8= |

Equations solver categories